Disseminated nocardiosis: report of five cases. Issue 4 (August 2015) - Branco, Lídia; Rodriguez-Nava, Veronica; Boiron, Patrick; Pinheiro, Dolores
Abstract : Introduction: Nocardiosis emerges as a serious infection in the immunocompromised patient, causing an aggressive clinical picture, which requires prolonged treatment. Case presentation: We present five cases of disseminated nocardiosis in patients under corticosteroid therapy with four different forms of clinical presentation. Conclusion: Immunocompromised patients are at increased risk of disseminated nocardiosis, which may require extended culture time for diagnosis and molecular methods. The cases emphasize the relevance of a careful evaluation of the central nervous system, a common target in nocardiosis dissemination.